2006
DOI: 10.1103/physrevb.73.024428
|View full text |Cite
|
Sign up to set email alerts
|

Tunable temperature-induced magnetization jump in aGdVO3single crystal

Abstract: Abstract:We report a novel feature of the temperature induced magnetization jump observed along the a-axis of the GdVO 3 single crystal at temperature T M ≈ 8 K.Below T M , the compound shows no coercivity and remanent magnetization indicating a homogenous antiferromagnetic structure. However, we will demonstrate that the magnetic state below T M is indeed history dependent and it shows up in different jumps in the magnetization only when warming the sample through T M . Such a magnetic memory effect is highly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…In the last case, GdVO 3 , the critical parameters obtained point to the 3D-Ising [21] has showed that it presents magnetic properties which make it quite different from the rest of the series and that, in particular, the a axis is indeed an easy axis, in agreement with our results.…”
Section: Critical Behavior: Fittings and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the last case, GdVO 3 , the critical parameters obtained point to the 3D-Ising [21] has showed that it presents magnetic properties which make it quite different from the rest of the series and that, in particular, the a axis is indeed an easy axis, in agreement with our results.…”
Section: Critical Behavior: Fittings and Discussionsupporting
confidence: 91%
“…Other differences arise in the particular direction in which the V 3+ spins are placed within the C-type spin ordered phase, which has not been studied for all ions yet. Literature results point to differences between the two big groups (La to Tb, Dy to Lu) [16], some cantings have been proposed [12,[17][18][19] and in some cases particular easy axes have been found for SmVO 3 [20] or GdVO 3 [21], while PrVO3 has been found to behave as a disordered antiferromagnet with random fields [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have already highlighted this special feature in GdVO 3 [17], and PrVO 3 [18]. A small TF in a superconducting magnet is inevitable unless the magnet is quenched.…”
Section: Iii-resultsmentioning
confidence: 85%
“…The experimental observations of exchange bias field in oxide coated cobalt and magnetization reversal in cobalt vanadate (IV) are known for a long time. 20,21 Recently, MR has been reported in several other systems such as Sr 2 RRuO 6 (R ¼ Yb, Y), 17,22,23 orthovanadates, 18,[24][25][26][27] orthoferrites, [28][29][30] orthochromites, [31][32][33][34][35][36][37][38][39][40][41] perovskite manganites, [42][43][44] and molecular magnets. [45][46][47] The mechanism of MR is found to be quite different in different systems.…”
Section: Introductionmentioning
confidence: 99%